Análise da relação valor de estoque e valor da empresa na indústria petrolífera - Ferreira, Liliam Rosalves (2006)
Inventories are an important component of companies assets in agriculture, mining, manufacturing and commerce sectors where they have a representative weight in the company valuation. The last decade was marked by important advances in inventories management, especially with Information Technology evolution. The oil industry has very peculiar challenges in inventories management due to a extensive global supply chain, with uncertainties about supply, pressures from ecologists, strong political issues and with great commodity prices variation verified during the last years. The subject has an increasing importance particularly regarding the market oil situation and with the general business environment that registers merger and acquisitions movements between companies which demands a necessary evaluation of the involved companies´ value. This work investigates the relationship between inventories´ value and companies´ value in order to identify whether or not a proper inventory management is related to company valuation by market value and also by Deducted Cash Flow (DCF). To develop this work, we carried and evaluated a quantitative research regarding performance data from 35 oil companies.. These companies are from different sizes and regions of the planet. The finding results indicate that the market does not penalize the oil companies inefficient inventories management., but the market gives a small award for the efficient companies. This award is larger than the one verified in previous studies with a wider range of activity sectors. For DCF valuation there is a small penalty for inefficient companies, however there is an excellent award for efficient companies. Considering other performance factors regarded in this study as control variables, efficient companies showed better general financial performance than the inefficient ones